(3OYGA GdehdO GdTQjas - (3GdbQTj GdJjej GdHcQj GdMfHdj, CHh GdaQL, GHf GdLhRj, LeGd GdOjf, YHO GdQMef Hf Ydj Hf eMeO, (B597 (3g`s ((3UGdM GdcGTas)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Gddge HLGg fHjc GdeUWai hMHjHc Udi Gddg Ydjg hSde Cf JLYd KhGH eG bO bQCfGgs
(3BNQgG (B:s
(3ehdGfG QH GdYGdejf SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf QHfG JbHd efG HjSQ ShQI GdaGJMI Bejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3 / 316s
(3eYLe GdeDdajf(B: (3L(B2 / 100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs